The Potential of Soil Bacterial Isolates from Liwa Botanical Gardens, West Lampung as Phosphate Solubilizing Bacteria - Ekowati, Cristina Nugroho; Shintia, Rina; Umar, Suratman; Irawan, Bambang (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2022)
Tanah Kebun Raya Liwa (KRL) Lampung Barat merupakan tanah jenis laterit yang kandungan unsur hara dan kesuburan tanahnya rendah, sehingga tidak dapat mendukung pertumbuhan tanaman hias yang ada secara optimal. Salah satu unsur hara yang penting dalam menunjang kesuburan dan pertumbuhan tanaman adalah fosfat. Jumlah fosfat terlarut dalam tanah yang dapat dimanfaatkan oleh tanaman sangat sedikit sehingga menyebabkan defisiensi. Bakteri pelarut fosfat asli dibutuhkan untuk memenuhi kebutuhan fosfat bagi tanaman. Tujuan dari penelitian ini adalah untuk mendapatkan isolat bakteri pelarut fosfat yang berpotensi melarutkan fosfat. Penelitian ini dilaksanakan pada bulan Maret sampai Juni 2021 meliputi isolasi bakteri pelarut fosfat dan pengujian potensi pelarutan fosfat pada media pikovskaya padat. Potensi bakteri pelarut fosfat ditentukan berdasarkan nilai Indeks Kelarutan Fosfat (IPF) tertinggi. Hasil isolasi tanah dari Kebun Raya Liwa diperoleh 10 isolat yang mampu melarutkan fosfat dan menghasilkan zona bening. Isolat dengan potensi pelarutan fosfat terbaik adalah isolat C1 dan C3 dengan nilai indeks pelarutan fosfat 2, 6 dan 2. Liwa Botanical Gardens (KRL) soil, West Lampung is a lateritic soil type nutrient content and low soil fertility, so it can’t support the growth of existing ornamental plants optimally. One of the important nutrients in supporting fertility and plant growth is phosphate. The amount of dissolved phosphate in the soil that can be utilized by plants is very small, causing a deficiency. Indigenous phosphate solubilizing bacteria are needed to meet the needs of phosphate for plants. The purpose of this study was to obtain isolates of phosphate solubilizing bacteria that have the potential to dissolve phosphate. This research was carried out from March to June 2021 covering the isolation of phosphate solubilizing bacteria and testing the potential for dissolving phosphate on solid pikovskaya media. Potential phosphate solubilizing bacteria were determined based on the highest Phosphate Solubility Index (IPF) value. The results of soil isolation from Liwa Botanical Gardens obtained 10 isolates capable of dissolving phosphate and producing a clear zone. Isolates with the best phosphate solubilizing potential were isolates C1 and C3 with phosphate solubilizing index values of 2, 6 and 2.